Heterogeneous expression of carcinoembryonic antigen in the normal colon and upregulation in active ulcerative colitis. - Smithson, J; Warren, B; Young, S; Pigott, R; Jewell, D (1996)
Using a technique of tolerization, a murine monoclonal antibody (MAb 2E8) has been raised which displays regional differences in reactivity in the epithelium of the normal human colon and increased reactivity in active ulcerative colitis. MAb 2E8 (IgG1) was highly colon-specific and gave higher immunoperoxidase staining scores in the proximal colonic mucosa compared with paired rectal sections (P < 0.02). Expression of the antigen reactive with MAb 2E8 was enhanced in active ulcerative colitis compared with quiescent ulcerative colitis (P < 0.05) and normal controls (P < 0.001). Western blotting and indirect immunofluorescent screening on transfected cell lines established that MAb 2E8 was reactive with carcinoembryonic antigen (CEA). This is the first demonstration of regional differences in the expression of CEA in the normal colon and indicates upregulation of this molecule in active ulcerative colitis.